1998
DOI: 10.1111/j.1472-8206.1998.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

A study comparing biopharmaceutic characteristics of four once daily controlled release diltiazem preparations

Abstract: In the present study we have compared the steady state biopharmaceutic characteristics of four diltiazem once daily controlled release capsules: Mono-Tildiem LP 300 (300 mg), Adizem XL (300 mg), Cardizem (300 mg) and Dilacor (240 mg). Sixteen healthy male volunteers (aged 22.9 +/- 3.3 years, range 19-31 years) completed an open label, multiple oral dose, randomized, four-period crossover study without a washout period in between. The volunteers received each diltiazem formulation once daily for four days. Trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several extended‐release (ER) formulations of diltiazem HCl have been introduced into the market over the past two decades, and pharmacokinetic characteristics of these products have been widely published 23 – 27 . To date, no diltiazem formulation has been developed for nighttime use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several extended‐release (ER) formulations of diltiazem HCl have been introduced into the market over the past two decades, and pharmacokinetic characteristics of these products have been widely published 23 – 27 . To date, no diltiazem formulation has been developed for nighttime use.…”
mentioning
confidence: 99%
“…22 Several extended-release (ER) formulations of diltiazem HCl have been introduced into the market over the past two decades, and pharmacokinetic characteristics of these products have been widely published. [23][24][25][26][27] To date, no diltiazem formulation has been developed for nighttime use. Recently, an innovative, extended-release formulation of diltiazem HCl that exhibits a unique dissolution profile, with a built-in lag time, was developed for nighttime dosing.…”
mentioning
confidence: 99%
“…These days diltiazem is readily measured in blood and so there are a number of published studies reporting on the concentration-response relationship for diltiazem [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, the literature on diltiazem is full of conflicting evidence because the limited original data correlating serum concentration with therapeutic effect have proved difficult to interpret.…”
Section: Minimum Effective Concentration and Minimum Effective Dosementioning
confidence: 99%
“…In a study comparing four different formulations of diltiazem, Hendriks et al [9] used a minimum effective concentration of 50 ng/ml as their cut-off point for the treatment of angina. They cited literature by Low et al [10] and Opie [11] to support this value.…”
Section: Minimum Effective Concentration and Minimum Effective Dosementioning
confidence: 99%
“…Propranolol is also approved for the prophylactic treatment of migraine although study data for chronic migraine has shown that there is no benefit from adding propranolol to patients insufficiently treated with topiramate . With the extended release once‐daily formulation, peak concentrations of diltiazem occur at 4–6 hours with elimination half‐life of 5–8 hours . Diltiazem undergoes extensive hepatic metabolism via CYP3A4 and CYP2D6 resulting in two major active metabolites, desacetyldiltiazem (DEA) and N‐desmethyldiltiazem (DEM), which are excreted primarily in the urine .…”
mentioning
confidence: 99%